Formulation and Evaluation of Pluronic lecithin Organogel of Nonsteroidal Anti inflammatory Drug for Topical Application - R, Choukse (International Journal of Pharmaceutical & Biological Archive, 2013)
Formulation and Evaluation of Pluronic lecithin Organogel of Nonsteroidal Anti inflammatory Drug for Topical Application